2015
DOI: 10.1377/hlthaff.2014.1384
|View full text |Cite
|
Sign up to set email alerts
|

Federal Parity Law Associated With Increased Probability Of Using Out-Of-Network Substance Use Disorder Treatment Services

Abstract: The Paul Wellstone and Pete Domenici Mental Health Parity and Addiction Equity Act of 2008 requires commercial insurers providing group coverage for substance use disorder services to offer benefits for those services at a level equal to those for medical or surgical benefits. Unlike previous parity policies instituted for federal employees and in individual states, the law extends parity to out-of-network services. We conducted an interrupted time-series analysis using insurance claims from large self-insured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(33 citation statements)
references
References 21 publications
2
31
0
Order By: Relevance
“…McGinty et al (McGinty et al, 2015) used 2007-2012 insurance claims data from members covered by large self-insured employers from the Truven Health MarketScan Commercial Claims and Encounters Database. Looking within a sample of people who used substance use disorder services, they used an interrupted time series design to determine that MHPAEA was associated with an increased probability of using out-of-network SUD services, with an increased average total spending on out-of-network SUD services, and with an increased average number of out-of-network outpatient SUD visits.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…McGinty et al (McGinty et al, 2015) used 2007-2012 insurance claims data from members covered by large self-insured employers from the Truven Health MarketScan Commercial Claims and Encounters Database. Looking within a sample of people who used substance use disorder services, they used an interrupted time series design to determine that MHPAEA was associated with an increased probability of using out-of-network SUD services, with an increased average total spending on out-of-network SUD services, and with an increased average number of out-of-network outpatient SUD visits.…”
Section: Literature Reviewmentioning
confidence: 99%
“…We examine all forms of treatment (inpatient, intermediate and outpatient) and we examine all BH services instead of focusing on SUD treatment only (Busch et al, 2014; McGinty et al, 2015). We also use four years of post-MHPAEA data to account for long-term effects and account for the impact of the IFR provisions (e.g., parity in NQTLs) in addition to the original MHPAEA provisions.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…15 McGinty et al found that MHPAEA was associated with increased access to, use of, and total spending on OON SUD services between 2007 and 2012, but did not consider in-network utilization or expenditures, and limited to users of SUD services, not all members. 16 Grazier et al found an association between MHPAEA and increases in outpatient mental health service use among high utilizers, but only studied data from one employer, and only considered changes between 2009 and 2010. 17 …”
Section: Introductionmentioning
confidence: 99%
“…Also, that study's main outcomes focused on SUD treatment, rather than all BH treatment. McGinty et al (2015) found that MHPAEA was associated with increased access to, use of, and total spending on out-of-network SUD services between 2007 and 2012. Although this study highlights a notable effect of MHPAEA, its focus on out-of-network care overlooks in-network care, which likely accounts for the majority of MH and SUD treatment.…”
Section: Introductionmentioning
confidence: 99%